Comparative Metabolite Profiling of Antarctic and Korean Mosses: Insights into Adaptation Mechanisms of Antarctic Moss Species - Marufa Naznin; Raisul Awal Mahmood; Md Badrul Alam; Kil Ho Shin; Kyungwon Min; Sang-Han Lee; Hyoungseok Lee; Sunghwan Kim (Plants, 2025)
This study investigates the relationship between secondary metabolites and stress tolerance in moss species, with a specific emphasis on comparing Antarctic and Korean mosses. Analyses of total phenolic content (TPC) and total flavonoid content (TFC) revealed that Antarctic mosses contain these compounds at significantly higher levels compared to the Korean mosses. These findings are consistent with greater antioxidant activities observed in Antarctic mosses through DPPH and ABTS•+ radical scavenging assays. In this study, a total of 620 metabolites were identified from the moss samples. The results showed that Antarctic mosses exhibited a high number and diversity of compounds including terpenoids, flavonoids, lipids, and other classes. Additionally, Antarctic mosses had fewer lipids with carbon chain lengths below 18 and a higher content of unsaturated lipids, indicating adaptations to maintain membrane fluidity under cold stress. The phylogenetic relationships suggested a correlation between metabolite profiles and genetic adaptations between these species. This research highlights the complex biochemical strategies that mosses, particularly those in Antarctic regions, employ to adapt the environmental stressors. The high abundance of secondary metabolites in Antarctic mosses not only serves as a defense mechanism against oxidative stress but also suggests their potential applications in various biotechnological aspects. This study reveals new avenues for exploring the ecological roles and potential uses of these resilient plant species.